REVEALING THE ABUSE OF DOMINANT POSITION BY MOTORCYCLES SALES INDUSTRY IN INDONESIA - Dinar Ayu Wulandari; Ria Setyawat (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Motorcycle company in Indonesia, namely Honda and Yamaha, violated the Law No. 5 of 1999 concerning the prohibition of monopoly and unfair business competition. Komisi Pengawas Persaingan Usaha (The Business Competition Supervisory Commission) as the responsible agency has issued the decision to resolve this case. However, on the other hand there is still alleged violation towards the dominant position abuse. Responding to the allegation, this study aims to analyze the accuracy of the decision which is given by the Business Competition Supervisory Commission in cases involving automatic scooter type motorcycle. The result of this study was the two companies not only violated Article 5 paragraph (1) of Law no. 5 of 1999 as decided by the Business Competition Supervisory Commission, but also allegedly violated the article 25 of Law No. 5 of 1999 related to the abuse of the dominant position in the price-fixing agreement which has been made by the automatic motorcycle companies of Honda and Yamaha.